Kedudukan Hukuman Mati Dalam KUHP Baru Perspektif Hak Asasi Manusia - Lubis, Muhammad Ridwan; Adi Syaputra, Muhammad Yusrizal (Universitas Medan Area, 2023)
This research aims to determine the position of death penalty law based on a human rights perspectiveafter the enactment of the new Criminal Code (KUHP). This research uses normative juridical methods,with qualitative analysis. The results of the research show that the old Criminal Code put the death penaltyas the main punishment, whereas in the new Criminal Code there is a shift in the position of the deathpenalty. After the enactment of the new Criminal Code, the death penalty was not immediately abolished,the death penalty still existed but alternative punishment was provided as a substitute for the deathpenalty. If we look at developing countries, the death penalty has begun to be abandoned because it isconsidered to violate human rights, in fact Indonesia is also aware of that, we can see in Article 28 A andArticle 28 Paragraph (2) of the Constitution of the Republic of Indonesia that the death penalty is it isagainst Human Rights.